2019
DOI: 10.1029/2018wr023217
|View full text |Cite
|
Sign up to set email alerts
|

Determining and Modeling Dominant Processes of Interrill Soil Erosion

Abstract: Understanding the dominant process of interrill soil erosion is imperative to better modeling interrill sediment delivery rates. The objectives are to (1) determine the limiting erosion process (detachment vs. transport) that controls interrill erosion under the study conditions, (2) quantify the effects of water and/or sediment influxes from upslope on downslope sediment transport and interrill erosion, and (3) evaluate the ability of commonly used hydraulic parameters for simulating interrill sediment delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Additionally, the sediment concentration of the sand-covered slope experienced little change when it began to generate runoff. Due to the weakened soil anti-erodibility and abundance of soil, the soil erosion process of sand-covered slopes was limited by the sediment transport capacity [24,25] .…”
Section: Soil Lossmentioning
confidence: 99%
“…Additionally, the sediment concentration of the sand-covered slope experienced little change when it began to generate runoff. Due to the weakened soil anti-erodibility and abundance of soil, the soil erosion process of sand-covered slopes was limited by the sediment transport capacity [24,25] .…”
Section: Soil Lossmentioning
confidence: 99%
“…We simply call for further investigations. These investigations could advantageously make use of the recent advances in computational fluid dynamics (Nouhou Bako et al, 2016, 2019.…”
Section: Mechanisms That Could Increase the Settling Velocitymentioning
confidence: 99%
“…In interrill areas, raindrop impacts and sheet flow are the main soil erosion drivers. Although their respective role and their interactions have driven many research works, it remains a subject of debate (Kinnell, 2005; Zhang, 2019). Numerous works have shown that the impacts of raindrops are a major contributor to sediment detachment for sheet flow (Moss, 1988; Moss & Green, 1983; Proffitt & Rose, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Development of process‐based models is a key research focus in water related research areas. In this context, the functioning of a hydrologic system is often depicted through a model that embeds various components, each associated with a mathematical formulation representing a given system process (Antonetti et al., 2016, 2017; Clark et al., 2015; Montanari & Koutsoyiannis, 2012; Zhang, 2019). Improving the performance of process‐based models requires identification of important processes.…”
Section: Introductionmentioning
confidence: 99%